Legitimization of Power and Sexual Violence in Religious Educational Institutions as Violations of Islamic Legal - Endri Yenti; Siska Mona Widia; Desi Asmaret; Syaflin Halim; Sofia Ridha (HUMANISMA : Journal of Gender Studies, 2025)
Islamic boarding schools are Islamic educational institutions in the form of dormitories where students' activities are carried out under the guidance and supervision of mentors who are supposed to play an important role in instilling religious values so that students can comply with the legal norms that apply to them. However, behind the image of Islamic boarding schools as places of spiritual development, reports of sexual violence have raised public concern because they are committed by people who have the authority to educate and protect students. This occurs because the perpetrators wield power, making it easy for them to intimidate their victims. Sexual violence in religious educational environments is often hidden and goes unreported because it is committed by people with strong power structures. This issue is important and very complex because it can lead to violations of Islamic legal norms. Using a qualitative approach, this study analyzes the experiences of victims and the response of institutions to violations that have occurred. The results of the study show that unchecked power can create an environment that encourages sexual violence. This is evidenced by the fact that the perpetrators were immoral teachers and dormitory supervisors who held positions of power at the Islamic boarding school, making it impossible for the victims to avoid or even reject them. This study is expected to provide insights into the need for policy reform and increased awareness to protect victims, as well as the enforcement of existing legal norms